Influence of Gmelina Wood on Mechanical Properties and Morphology of Epoxy Composites - Prakoso, Agung; Pratiwi, Henny (Sekolah Tinggi Teknologi Adisutjipto, 2018)
Lignocellulosic filler such as gmelina wood flour is an alternative of synthetic reinforcements which is ecofriendly, abundant in nature and inexpensive. This research aims to investigate the effects of gmelina wood filler addition on tensile properties, impact strength and morphology of epoxy composites. Filler volume fractions evaluated were10, 20, 30 and 40 percent with 30 mesh filler size. Hand lay-up method was used to manufacture the composites. Tensile strength, tensile modulus, elongation and impact strength were determined based on ASTM standard. Results show that filler addition up to some extents improves the mechanical properties of materials. The optimum tensile properties and impact strength are achieved when 10 percent filler is added into epoxy matrix. Further addition of filler degrades the tensile and impact properties of composites. This phenomenon is due to the existence of weak interfacial interaction between the gmelina wood filler and epoxy matrix for higher filler volume concentration beyond 10 vol. %. The scanning electron micrograph of tensile fracture surface reveals that there are voids, agglomeration and pull-out mechanism which are the cause of the composites failure.